Risk-taking by Russian banks: do location, ownership and size matter? - Zuzana Fungáčová; Laura Solanko (Bank of Finland, Institute for Economies in Transition (BOFIT), 2008)
The Russian banking sector has experienced enormous growth rates during the last 6-7 years. The rapid growth of assets has, however, contributed to a decrease in the capital adequacy ratio, thus influencing the ability of banks to cope with risk. Using quarterly data spanning from 1999 to 2007 on all Russian banks, we investigate the relationship between bank characteristics and risk-taking by Russian banks. The analysis of financial ratios reveals that, on average, the risk levels are still below those observed in Central and Eastern Europe. Combining the group-wise comparisons of financial ratios and the results of insolvency risk analysis based on fixed effects vector decomposition, three main conclusions emerge. First, controlling for bank characteristics, large banks have higher insolvency risk than small ones. Second, foreign-owned banks exhibit higher insolvency risk than domestic banks and large state-controlled banks are, unlike other state-controlled banks, more stable. Third, we find that the regional banks engage in significantly more risk-taking than their counterparts in Moscow.
URN:NBN:fi:bof-201408072170
Keywords: G21; G32; P34; 330; bank risk-taking; banks in transition; Russia